A Comparative Analysis of the Economic Burden of Breast, Colorectal and Lung Cancer-Related Premature Mortality in Slovenia: Value-Added Decomposition by Occupation-Gender Groups - Tjaša Redek; Tanja Istenič; Petra Došenović Bonča; Ivica Ratoša; Andraž Perhavec; Daša Farčnik (Slovenian Journal of Public Health, 2026)
Abstract Introduction This paper aims to estimate the value-added loss attributable to premature deaths from breast, colorectal and lung cancer in Slovenia using a novel methodology using linked employer-employee data, enabling value-added decomposition by occupation-gender groups. Methods The analysis is based on population-level microdata for the 2016–2022 period matched from several sources. Premature mortality costs are estimated using occupation- and gender-specific output losses rather than assuming uniform productivity across working-age individuals. We approximate intangible capital using each firm's occupational and gender structure and estimate productivity losses due to premature mortality by specific occupation, revealing differences in the economic footprint of different cancer types. Results On average, the loss of value added from a premature death due to colorectal cancer is between €352,000 and €392,000, from lung cancer, on average, between €150,000 and €178,000 and from breast cancer, around €436,000. In total, given that Slovenia's GDP in 2024 was around €66 billion (€52 billion at constant 2015 prices), the total value-added loss associated with these three cancer types amounted to about 0.5% of Slovenia's 2024 GDP. Over the study period, premature mortality attributable to these cancers translated into an estimated cumulative (current and future) GDP loss of roughly €371 million. Conclusions Results indicate that notable reductions in indirect costs could be achieved in Slovenia through efficient and effective measures to manage the burden of cancer, including cancer screening programmes, other primary prevention approaches, timely access to diagnostics and treatment, and return-to-work policies.